Juvenile ossifying fibroma: case report and literature review. Management and differential diagnosis - Lemoine Sarah; Cassagnau Elisabeth; Bertin Hélios; Poisson Maria; Corre Pierre; Guiol Julien (EDP Sciences, 2018)
Introduction: Juvenile ossifying fibroma (JOF) is a rare neoplasm characterized by the replacement of the normal bone matrix with osteo-fibrous tissue. It has the tendency to be locally aggressive despite its benign character and to have a strong tendency for recurrence. Observation: In this case report, the patient is a young man, aged 16, with rapidly advancing maxillary swelling. We describe the diagnostic procedure, the surgical procedure and the differential diagnosis to be eliminated. Discussion: The clinical presentation of JOF, and its rapid growth, can cause fear of other pathologies such as osteosarcoma. The radiological characteristics should reassure the practitioner and a histological examination confirmed the diagnosis. Conclusion: JOF is a benign tumor. It should be operated on at an early stage because of its rapid growth. In its clinical and histological presentation, its trabecular form may mimic an osteosarcoma.